A character study: the influence of heredity and environment upon character - Lill, Gertrude (My University, 1907)
Introduction: Character is that quality of moral force inherent in an individual, which leads to a line of conduct conformable to that quality. Character is a positive, not a negative virtue, and is developed through daily habits of self discipline and high thinking, consciously and unconsciously practiced from childhood. The man of character moves among his fellow men surrounded by an atmosphere of moral influence of decided but unobtrusive force unless the occasion demands it, which makes itself felt wherever his duty may call him. It is to such men and women that individuals and communities turn in times of stress, and it is such men and women we would have our children become. What decides the character of an individual. The great factors are heredity and environment, and the influence of each on character will now be briefly presented.
Citation: Lill, Gertrude. A character study: the influence of heredity and environment upon character. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Character Development; Heredity; Environmental Influences; Theses